RETRACTED: Barriers and facilitators of childhood obesity prevention policies: A systematic review and meta-synthesis - Taghizadeh, Shahnaz; Hashemi, Mohamad Ghazanfari; Zarnag, Rahim Khodayari; Fayyazishishavan, Ehsan; Gholami, Marjan; Farhangi, Mahdieh Abbasalizad; Gojani, Leila Jahanbazi (Frontiers in Pediatrics, 2023)
Objectives: Childhood obesity is one of the worldwide considerable public health challenges, that many factors can play a role in its management. So, this article examined qualitative studies of facilitators and barriers of childhood obesity prevention (COP) policies. Methods: A systematic review of SCOPUS, PubMed and Google scholar databases was performed between 1/1/2010 to 7/11/2020. All articles were considered as eligible when they published between 1/1/2010 to 7/11/2020, which examined factors that influence the implementation of COP policies at a community approach. Results: The parent’s reluctance to engagement in childhood obesity prevention (COP) activities, lack of sufficient knowledge and financial problems in the individual level, and the beliefs on COP in sociocultural level and limited funding and resources, time limitations in stakeholders in the implementation level, lack of policy support in the structural level were the most frequently reported barriers. Also, an effective communication between stakeholders and parents and school staff in the sociocultural level and flexibility of the intervention, delivery of healthy food program in schools, low-cost and appropriate resources, the availability of appropriate facilities are the most frequently reported facilitators in the structural level. Conclusions: individual, sociocultural, and structural level related barriers and facilitators influence the implementation of COP policies. Most of the barriers and facilitators in this systematic review were related to the structural level.